Pengaruh Stres Kerja, Komunikasi dan Keterlibatan Kerja Terhadap Kepuasan Kerja Karyawan Di Grand Mercure Medan Angkasa Hotel - Syazida, Shafa; Ardiani, Winda; Suvero Suhya, Annisa (Yayasan Cita Cendekiawan Al Khwarizmi, 2022)
This study aims to determine whether work stress, communication and work involvement affect employee job satisfaction at Grand Mercure Medan Angkasa Hotel. The research design of multiple linear regression analysis wa used to find out how the influence between the independent variables on the dependent variable was. This research uses quantitative research in the form of associative. The population in this study used a saturated sample, therefore the sample of this study was 115 employees, which included all employees at Grand Mercure Medan Angkasa Hotel. The results of this study indicate that the work stress variable has no significant effect on employee job satisfaction, the communication variable has a significant effect on employee job satisfaction, work involvement has a significant effect on employee job satisfaction, and work stress, communication and work involvement have a positive and significant effect on employee job satisfaction at Grand Mercure Medan Angkasa Hotel.